PSYCHOLOGICAL FEATURES OF AGGRESSION IN ADOLESCENTS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
It is necessary to identify the causes of the manifestation of aggressive behavior observed in adolescents today, to prevent or control destructive behavior. This article discusses the psychological characteristics of aggression in adolescence, changes in behavior, and the formation of aggressive behavior in adolescence. It also discusses the psychological characteristics of violence, the reasons affecting its formation in adolescence, and modern research by scientists on this problem.